New Synthetic Routes to Polyoxometalate Containing Ionic Liquids - Herrmann, Sven (Springer, 2015)
In his Master project Sven Herrmann for the first time carried out fundamental investigations into the development of polyoxometalate based ionic liquids (POM-ILs). The POM-ILs were obtained by charge balancing inorganic polyoxometalate (POM) anions with sterically demanding tetraalkylammonium or tetraalkylphosphonium cations. By functionalization of lacunary Keggin clusters with 3d-transition metals and charge balancing with tetraalkylammonium cations of differing chain length, a model system for the correlation of the molecular structure with macroscopic materials properties was obtained. In a systematic approach the syntheses via self-aggregation is presented. Analytic methods comprise UV-Vis, FTIR, NMR, EPR and Mößbauer spectroscopy. For determination of the materials properties TGA and DSC were carried out and rheological studies shed light onto the flow characteristics of the highly viscous materials.